Help your kids with computer coding : a unique step-by-step visual guide, from binary code to building games - Vorderman, Carol; Woodcock, Jon.; McManus, Sean, 1973-; Steele, Craig; Quigley, Claire; McCafferty, Daniel (New York, New York : DK Publishing, 2014)
This unique guide is full of fun exercises and helpful tips that will help children learn all aspects of coding. Step-by-step explanations make the complex art of programming clear, teaching the basics of JavaScript, Python, and C++. Eventually building to more advanced projects, Help Your Kids with Computer Coding will have children and parents alike creating their own games, apps, 3-D models, animations, and websites in no time.
What is coding? -- Starting from scratch -- Playing with Python -- Inside computers -- Programming in the real world.
Includes index.
Keywords: Computer programming; Computer programming -- Study and teaching